Roles of cytokine storm in sepsis progression: biomarkers, and emerging therapeutic strategies - You, Weibin (Frontiers in Immunology, 2025)
Sepsis is a life-threatening syndrome marked by uncontrolled systemic inflammation, cytokine storm, and organ dysfunction. Central to its pathogenesis is innate immune hyperactivation, which triggers excessive cytokine release and inflammatory cell death, ultimately driving multiorgan failure. Despite advancements in intensive care, immune dysregulation remains a major therapeutic hurdle. Moreover, recent discoveries of emerging biomarkers, such as serum amyloid A (SAA), high-density lipoprotein (HDL), monocyte distribution width (MDW), neutrophil-to-lymphocyte ratio (NLR), and RDW-to-albumin ratio (RAR), highlight their potential diagnostic and prognostic value. This review systematically summarizes the cellular and molecular mechanisms underlying cytokine storm, emphasizing the roles of TNF-α, IL-1β, IL-6, and inflammasome activation. Furthermore, we outline current and emerging therapeutic strategies targeting both immune overactivation and late-stage immunosuppression, including cytokine antagonists, immune checkpoint inhibitors, and nanomedicine-based approaches, providing a comprehensive framework to guide precision immunotherapy in sepsis management.